(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
Drawing on the debates on reenactment proposed by André Lepecki and Rebecca Schneider, the article proposed that works presented as original be understood as reenactments, in order to reveal the invisible co-authorships that inhabit them. The study focused on Ruth St. Denis’s 1906 performance Radha, considered one of the pioneering works of American modern dance. As demonstrated by Priya Srinivasan’s research, Radha was developed through the appropriation of the precarious labor of Indian artists circulating within a global cultural market.